Empowering farmers' independence and boosting local economy through regenerative farming and Islamic contracts in Goa Village, West Sumbawa - Ahlis, Fatoni; Mega TR, Luik; Adam Sa'ad, Auwal; Ferdi Zanuar, Azan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Sunan Giri Bima, 2023)
The current conventional agriculture practice cannot be separated from industrialized. This can be seen from farmers' dependence on input materials such as seeds, synthetic fertilizers, and synthetic pesticides. Industrialists then use the powerlessness of these farmers to continue to make them dependent and require planting costs that can be avoided, especially concerning these inputs. In Islam, the farmer is called fallahun, which means success, glory, and happiness. Through regenerative farming, farmers' problems related to dependence on planting inputs can be reduced or even eliminated. Besides, it can also develop the local economy and be ensured that regenerative farming cannot cause environmental damage as caused by conventional farming. In addition, Islam is very concerned with the development of agriculture, which is marked by the availability of specific agricultural contracts, such as musaqah, muzara'ah, and mukhabarah, also other partnership contracts, such as mudharabah and musyarakah. Therefore, this paper will discuss how Islam views conventional agriculture and how farmers can gain independence through regenerative farming and Islamic understanding, which can boost the local economy. This qualitative study uses the descriptive-analytical method and a literature review.